Ambient Air Quality in the Czech Republic (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Ambient air quality in the present-day Czech Republic (CR), one of the two succession countries of Czechoslovakia post-1993, was perceived as a major problem with severe human health and environmental consequences, particularly between the 1970s and 1990s. Since that time, the ambient air quality in the CR has improved substantially, due to newly introduced stringent legislation and technical countermeasures. Nevertheless, there are still activities which represent significant emission sources, such as local heating and increased vehicle travel through communities. After a substantial decrease in emissions in both the CR and its neighbouring countries, the levels of some ambient air pollutants from the 2000s are still not satisfactory. In this respect, aerosol, ground-level ozone, and benzo[a]pyrene remain major problems, as they do elsewhere in Europe. The book provides a valuable update both on time trends and spatial changes in ambient air quality, and highlights the recent activities in both monitoring and modelling of principle ambient air pollutants in the CR.